COLLABORATION BETWEEN ECONOMIC OPERATORS SITUATED IN THE WARMIA AND MAZURY REGION AND BUSINESS ENVIRONMENT INSTITUTIONS - Pukin, Paulina (Acta Universitatis Nicolai Copernici. Zarządzanie, 2019)
Competitiveness of enterprises in North-East Poland is the lowest in this country. Firms in Warmia and Mazury voivodeship need institutional support  from private and public sector. Collaboration between economic operators and business environment institutions is an important issue. Business environment helps boost entrepreneurship and innovation of firms. The core research objective of this article is to diagnose and evaluate the collaboration between economic operators situated in the Warmia and Mazury region and business environment institutions. The research method applied: statistical surveys based on surveys research. Questionnaire was used as a tool in the research. Research conducted at the turn of 2018 and 2019 among 21 economic operators located in the region of Warmia and Mazury (especially in Olsztyn – the biggest city in the region). Economic operators collaborate more often with BEIs from the Warmia and Mazury region than with BEIs from other regions. Most economic operators are not satisfied with the collaboration with BEIs from Warmia and Mazury voivodeship due to lack of important services and activities offered by the institutions, existing barriers and obstacles, as well as the low quality of services offered in the Warmia and Mazury region. The most significant barriers and obstacles to collaboration with BEIs include considerable formalisation and bureaucracy, insufficient skills of personnel, and long waiting time for starting collaboration